A Multidisciplinary Intervention in Childhood Obesity Acutely Improves Insulin Resistance and Inflammatory Markers Independent From Body Composition - Mayerhofer, Ernst; Ratzinger, Franz; Kienreich, Nina Elvira; Stiel, Annika; Witzeneder, Nadine; Schrefl, Eva; Greiner, Georg; Wegscheider, Christoph; Graf, Irene; Schmetterer, Klaus; Marculescu, Rodrig; Szekeres, Thomas; et al. (Frontiers in Pediatrics, 2020)
Childhood obesity is an increasing health care problem associated with insulin resistance and low-level systemic inflammation, which can ultimately lead to diabetes. Evidence for efficacy of therapeutic intervention programs on the early development of obesity associated sequelae is moderate. This paper investigates the effect of a multidisciplinary short-term intervention program on insulin resistance and metaflammation in childhood obesity. Two hundred and thirty-six overweight or obese children and adolescents between the ages of 10 and 14 were included in a prospective five-month intervention study, which included sports, psychotherapy, and nutritional counseling. Primary endpoints were the effects on body mass index standard deviation score (BMI-SDS) and homeostatic model assessment of insulin resistance (HOMA-IR), key secondary endpoints were the levels of C-reactive protein (CRP), leptin, and adiponectin. At baseline, a substantial proportion of participants showed signs of insulin resistance (mean HOMA-IR 5.5  3.4) despite not meeting the diagnostic criteria for diabetes, and low-level inflammation (mean CRP 3.9 mg/l  3.8 mg/l). One hundred and ninety-five participants (83%) completed the program resulting in a significant reduction in BMI-SDS, HOMA IR, CRP, and leptin and a significant increase in adiponectin (mean change compared to baseline -0.14, -0.85, -1.0 mg/l, -2.8 ng/ml, and 0.5µg/ml respectively; p < .001 each). Effects on BMI SDS, HOMA IR, CRP, and adiponectin were largely independent whereas leptin was positively correlated with BMI-SDS and total fat mass before and after intervention (r = 0.56 and 0.61, p < .001 each). Short-term multidisciplinary intervention successfully improved body composition, insulin sensitivity, low-level systemic inflammation, and metabolic profile of adipose tissue in childhood obesity. Our findings highlight the immediate connection between obesity and the pathophysiology of its sequelae, and emphasize the importance of early intervention. Continued lifestyle modification is likely necessary to consolidate and augment the long-term effects.